Implementation of Enterprise Resource Planning (ERP) Based Information System Using Odoo Software - Utami, Mega Putri; Kharisma, Ivana Lucia (The Eastasouth Journal of Information System and Computer Science, 2023)
Management and good data management is something that is very important for the continuity of a company. With management in a company, it is expected that all actions or activities carried out will run well and be controlled. The research focused on the use of an Enterprise Resource Planning (ERP) Based Information System using the odoo software used in the Purchasing & Materials department or more specifically known as PPIC. The purpose of this research is to find out how the use of ERP technology can facilitate coordination and communication between users so as to produce fast decision making. The implementation of this information system is expected to be one of the solutions in overcoming the problems that exist at PT Longvin Indonesia, especially the PPIC department.